Les fibules ansées de tradition germanique orientale provenant de la nécropole Saint-Chéron à Chartres (Eure-et-Loir) - Michel Kazanski (Revue Archéologique du Centre de la France)
Two crossbow fibulae, belonging to the clothing tradition of the Eastern Germans, were unearthed in a tomb (n ° 94) in the necropolis of Saint-Chéron, in Chartres (France). These fibulae are derived from those of the Ambroz 16/4-III type, belonging to the late Roman period and characteristic of the Chernyakhov culture (in the southern part of Eastern Europe), i.e. Germanic and non-Germanic population (the Goths and their allies). These fibulae are attested, yet more scarcely, on the sites of the cultures of Wielbark and Przeworsk in the Vistula basin, belonging to the Eastern Germans. These fibulae from Eastern and Central Europe are dated from the 3rd and the 4th centuries. Concerning the time of the Great Migrations, mainly for the 5th century, crossbow fibulae derived from those of Ambroz 16/4-III are rare and attested outside of the main area of ​​distribution of their prototypes: in the North-East of the Black Sea (1 site), in Spain (1 site), in Italy (1 site) and especially in Gaul (3 sites). Fibulae of the Ambroz 16/4-III type and their derivatives were found mainly in the area of ​​activity of the Goths during the Roman Period and the Great Migrations, between the Vistula, the Black Sea and the Iberian Peninsula. The few fibulae of this type discovered elsewhere, in Northern Gaul for example, probably attest to the displacement of isolated individuals. Indeed, in the tomb of Saint-Chéron, the position of the pair of fibulae, on the thorax, is entirely in accordance with that adopted by the Eastern Germans in Roman times.